Paraguay : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 2001)
The report provides an overview of the recent economic developments in Paraguay. The study analyzes the potential output, growth, prices, wages, and the labor market; and assesses the public finances, social security, and public enterprises. The paper reviews the monetary sector, evaluates the soundness of the banking sector and its developments, the external sector by assessing the balance-of-payments developments and the exchange and trade system. The study also provides a statistical appendix report of the country.